A role for Myo-II zipper and spaghetti squash in Gliotactin-dependent Drosophila melanogaster wing hair planar cell polarity. - Chase Holland; Natalya Cox; Hanna Dery; Mariah Williams; Gwendolyn Jones; Lindi Newton; Kristin Jurgensen; Han Chang; Alex Hord; Won Chang; Damon Montgomery; Hawkins Hochstedler; et al. (PLoS ONE)
Planar cell polarity, polarization in the plane of an epithelium, is critical for tissue development. The Drosophila melanogaster wing epithelium is an important model system for planar cell polarity establishment and has greatly informed studies in vertebrates. The well-studied Frizzled-dependent and Fat - Dachsous - Four-jointed pathways establish proximal-to-distal polarity of wing hairs, while a Frizzled-independent mechanism mediated by septate junction proteins Gliotactin, Coracle, and Varicose is required for parallel alignment of neighboring hairs. In this study, we explore a requirement for the non-muscle myosin II proteins Spaghetti Squash and Zipper in wing hair planar cell polarity. We confirm a previously recognized role in hair initiation and demonstrate a second, novel Gliotactin-interacting requirement for spaghetti squash and zipper in parallel alignment. Immunolabeling experiments demonstrate that Spaghetti Squash and Zipper localize to the base of the developing hairs during the same time frame that septate junction proteins transiently relocalize to the apical cell surface. This localization is abrogated in Gliotactin loss-of-function genotypes. We propose that Gliotactin promotes Spaghetti Squash and Zipper accumulation at the cell apical surface during wing hair extension and that this apical Myosin-II complex stabilizes the developing hair base, maintaining parallel alignment of neighboring wing hairs.